Computational processing and the translation of the Arabic phonemic system (its roots and branches) into a matrix. - zellagui., houria (El Omda in Linguistics and Discourse Analysis, 2023)
Computing and translating the Arabic vocalic system (ascendants and descendants) into a Matrice Abstract: In the context of Arabic language computing, this paper attempts to create mathematical formulation of Arabic phonetic descriptions in line with the technical and digital development that has been accessed to the world's languages; since it is interested in the analysis of Arab vowels, which are considered as acounterpart of consonantin the generalphonetic system of the Standard Arabic; given that it proceeds from the division that makes it an ascendants and descendants, demonstrates the characteristics of its units and their relationships with Phonetics, and is specifically concernedby examining the relationship betweenascendants and descendants, which allows them to be translated into matrix by mathematical concept. The study aspires to establish an Arabic vocalic system with ascendants and descendants in order to be able to respond to automated programming, which in turn creates the Arabic language at the phonetic level of computers, as well as other partial systems at the levels of study analysis. Keywords: Computing - Vowels -Arabic phonetic system - Mathematic formulation - ascendants and descendants– Matrices